2008
DOI: 10.1002/jor.20597
|View full text |Cite
|
Sign up to set email alerts
|

EWS/FLI1 suppresses retinoblastoma protein function and senescence in Ewing's sarcoma cells

Abstract: Ewing's Family Tumors (EFTs) most commonly harbor a specific t(11;22) translocation that generates the EWS/FLI1 fusion protein responsible for malignant transformation. Many potential downstream targets of EWS/FLI1 have been identified but a detailed mechanism by which the fusion protein brings about transformation remains unknown. In this report, we show that depletion of EWS/FLI1 in Ewing's cell lines results in a senescence phenotype, a marked increase in expression of the G1/S regulatory proteins p27 kip1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
6
19
0
1
Order By: Relevance
“…Previous evidence has indicated that direct depletion of EWS/FLI1 in ES cell lines induces a senescence phenotype [38]. Knockdown of EWS/FLI1 was also coupled to decreases in cyclin D1 and promotion of p53 expression [38, 39] which were observed after EGFR inhibition in our experiments. Thus, activities displayed by an EGFR inhibitor are consistent with other experimental agents that induce antiproliferative effects in ES associated with stimulation of p53 expression [40-42].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previous evidence has indicated that direct depletion of EWS/FLI1 in ES cell lines induces a senescence phenotype [38]. Knockdown of EWS/FLI1 was also coupled to decreases in cyclin D1 and promotion of p53 expression [38, 39] which were observed after EGFR inhibition in our experiments. Thus, activities displayed by an EGFR inhibitor are consistent with other experimental agents that induce antiproliferative effects in ES associated with stimulation of p53 expression [40-42].…”
Section: Discussionsupporting
confidence: 69%
“…Also, the EGFR inhibitor increased the fraction of cells in senescence, i.e., in a stable state of cell cycle arrest [37]. Previous evidence has indicated that direct depletion of EWS/FLI1 in ES cell lines induces a senescence phenotype [38]. Knockdown of EWS/FLI1 was also coupled to decreases in cyclin D1 and promotion of p53 expression [38, 39] which were observed after EGFR inhibition in our experiments.…”
Section: Discussionsupporting
confidence: 58%
“…26 Also, reduction of EWS-FLI1 protein levels can lead to G 1 arrest by increasing the cyclin-dependent kinase inhibitors (p27 Kip1 and p57 Kip2 ) expression and increasing pRB protein. 27 EWS-FLI1 affects the transcription of a large number of proteins that function in the regulation of the cell cycle, 28 supporting our findings that ESAP1 interrupts cell cycle kinetics at important downstream pathways from EWS-FLI1.…”
supporting
confidence: 72%
“…EWSR1-null spermatocytes are deficient in XY bivalent formation and have reduced meiotic recombination, resulting in massive apoptosis and complete arrest in gamete maturation. Notably, the homozygous EWSR1-null mice also show premature cellular senescence in embryonic fibroblasts (Li et al 2007) and hematopoietic stem cells (Cho et al 2011), an effect that seems to be mediated by hypophosphorylation and functional activation of the retinoblastoma (pRb) family of proteins (Hu et al 2008a).…”
Section: Ewsmentioning
confidence: 99%